Synthesis of new 1, 2-dideoxy C-linked carbo-β-amino acids and α/β-peptides with 11/9-helix, helix-turn and helix-turn-helix structures. Issue 42 (18th October 2018) - Adepu, Ramesh; Kanakaraju, Marumudi; Chandramouli, Nagula; Reddy, Purushotham P.; Sharma, Gangavaram V.M.; Sarma, Akella V.S.; Kunwar, Ajit C.
Abstract: The present study describes the synthesis of new C-linked carbo-β-amino acids [β-Caa( 1, 2-ddx ) ], with a 1, 2-dideoxy D- xylo furanoside side chain (a tetrahydro furan derivative). The stereochemistry at the newly created amine centers was determined by modified Mosher method. The ( S )-β-Caa( 1, 2-ddx ) prepared fromd -mannose diacetonide were utilized for the synthesis of 1:1 α/β-peptides with L-Ala. The conformational analysis (NMR, MD and CD) revealed the presence of 11/9-helix, helix induced helix-turn (HT) and helix-turn-helix (HTH) in these peptides. These side chains with tetrahydrofuran ring facilitated the formation of robust helix, unlike some other side chains from earlier studies. Graphical abstract: